2021
DOI: 10.3847/1538-3881/abfec4
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Abundances in M31: Gradients in the Giant Stellar Stream*

Abstract: We analyze existing measurements of [Fe/H] and [α/Fe] for individual red giant branch (RGB) stars in the Giant Stellar Stream (GSS) of M31 to determine whether spatial abundance gradients are present. These measurements were obtained from low-(R ∼ 3000) and moderate-(R ∼ 6000) resolution Keck/DEIMOS spectroscopy using spectral synthesis techniques as part of the Elemental Abundances in M31 survey. From a sample of 62 RGB stars spanning the GSS at 17, 22, and 33 projected kpc, we measure a [Fe/H] gradient of −0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 116 publications
(331 reference statements)
2
25
2
Order By: Relevance
“…As previously established, the NE shelf metallicity distribution can place unique constraints on GSS formation models that track metallicity because the metal-rich central debris of the progenitor most likely pollutes this region (Fardal et al 2008;Miki et al 2016;Kirihara et al 2017). For example, Miki et al (2016) predicted that an observed negative metallicity gradient in the GSS (Ibata et al 2007;Gilbert et al 2009;Conn et al 2016;Cohen et al 2018;Escala et al 2021) should result in higher metallicity for the NE shelf than other GSS-related tidal structures, whereas the W shelf and GSS metallicity should be comparable (as found by F12). 18 In contrast, the NE shelf metallicity distribution appears to be consistent with that of the W shelf and GSS (Section 5.2) rather than being more metalrich.…”
Section: Implications For Gss Merger Scenariosmentioning
confidence: 71%
See 1 more Smart Citation
“…As previously established, the NE shelf metallicity distribution can place unique constraints on GSS formation models that track metallicity because the metal-rich central debris of the progenitor most likely pollutes this region (Fardal et al 2008;Miki et al 2016;Kirihara et al 2017). For example, Miki et al (2016) predicted that an observed negative metallicity gradient in the GSS (Ibata et al 2007;Gilbert et al 2009;Conn et al 2016;Cohen et al 2018;Escala et al 2021) should result in higher metallicity for the NE shelf than other GSS-related tidal structures, whereas the W shelf and GSS metallicity should be comparable (as found by F12). 18 In contrast, the NE shelf metallicity distribution appears to be consistent with that of the W shelf and GSS (Section 5.2) rather than being more metalrich.…”
Section: Implications For Gss Merger Scenariosmentioning
confidence: 71%
“…Furthermore, the NE shelf metallicity distribution could be used to infer the properties of the progenitor, as the shelf region is predicted to contain its metal-rich central debris (Mori & Rich 2008;Fardal et al 2008;Miki et al 2016;Kirihara et al 2017). The observed metallicity gradient(s) in the GSS (Ibata et al 2007;Gilbert et al 2009;Conn et al 2016;Cohen et al 2018;Escala et al 2021) could be combined with the metallicity distributions of the NE, W, and SE shelves to connect chemical variations on the sky to the intrinsic properties of the progenitor (Fardal et al 2008;Miki et al 2016;Kirihara et al 2017;Milošević et al 2022). This metallicity mapping may be crucial for distinguishing between major and minor merger scenarios for the formation of the GSS and shelves (see the discussions of Gilbert et al 2019;Escala et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing this publication, we are privileged to have spectroscopic metallicities measured for millions of stars in the MW. Furthermore, the deeper spectroscopic observations of M31 have enabled α-abundance measurements and iron metallicities derived from full spectral synthesis for an evergrowing sample of individual stars in M31ʼs halo (Vargas et al 2014b;Escala et al 2019Escala et al , 2020aEscala et al , 2020bEscala et al , 2021Gilbert et al 2019Gilbert et al , 2020 and M31ʼs satellites (Vargas et al 2014a;Kirby et al 2020;Wojno et al 2020). With more knowledge than ever about the chemodynamical structure of the LG, we are now in a position to explore more deeply the potential of utilizing CARDs to constrain the formation histories of LG galaxies, and address how this method might aid in identifying the stars that were born in high-redshift, low-mass galaxies that cannot be observed directly.…”
Section: Introductionmentioning
confidence: 99%
“…From photometry, Conn et al (2016) determined the GSS to be metal-rich, with the bulk of the stars having −0.7 [Fe/H] −0.2. Escala et al (2021) further find GSS stars to have elevated [α/Fe] ratios, suggesting that they originated in a massive galaxy.…”
Section: The Giant Stellar Streammentioning
confidence: 77%